Implikasi Kurikulum Bahasa Arab Integratif terhadap Keterampilan Berbahasa Siswa - Nur Roziqin, Muhammad; Khasanah, Fitrohtul; Daimah (Kartika: Jurnal Studi Keislaman, 2025)
Arabic language learning is directed toward the mastery of language skills, including listening (al-istimā’), speaking (al-kalām), reading (al-qirā’ah), and writing (al-kitābah). This implies that Arabic instruction is expected to enable learners to communicate both receptively and productively. At the Islamic Program of MA An-Nawawi Berjan Purworejo, an integrative Arabic curriculum has been implemented since the program’s inception as part of its traditional pesantren-based educational system. This approach blends traditional and modern elements, including madrasah dīniyyah instruction and immersive Arabic language practices in the dormitory environment. This study aims to analyze the implications of the integrative curriculum on students’ skills. A qualitative descriptive method with a phenomenological approach was used, involving observation, documentation, and in-depth interviews. The results reveal that the integrative curriculum fosters a contextual and comprehensive learning environment, enhances active student participation, strengthens grammatical understanding, and builds students’ confidence in using Arabic. The findings are analyzed through the psychological lenses of behaviorism and constructivism.